Penerapan Algoritma Tibrewala, Philippe dan Browne Untuk Pembuatan Jadwal Karyawan Pada Restoran Tea Garden - Witani Gea, Efan Hasrat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Manpower scheduling is the allocation of human resources at work stations according to the needs, to increase productivity the company must schedule the workforce optimally. Tea Garden Restaurant is a restaurant that produces fast food products located in Medan City. In allocating labor, the restaurant has implemented a workforce scheduling with 3 work shifts and 1 day off in 1 week. Human resources are very important to note. To accommodate 3 work shifts per day and 1 day off in 1 week, this study used a modified Tibrewala, Philippe and Browne algorithm. The algorithm modification changes and adds from 3 steps to 5 steps and changes the tabular table format of labor scheduling for three shifts. Scheduling a workforce of 6 working days and 1 day off requires a workforce of 20 people. If there is an excess of labor, it is used when there are workers who do not come to work because of illness, permission or leave. The scheduling is expected to maintain the health and safety of workers so that they can do optimal work to increase restaurant productivit